Herbivore functions in the hot-seat: Resilience of Acanthurus triostegus to marine heatwaves. - Taylor Souza; Jeroen Brijs; Leon Tran; Larry Crowder; Jacob L Johansen (PLoS ONE)
Herbivorous fishes play a crucial role in the conservation of coral reefs threatened by thermal stress (e.g., marine heatwaves and long-term ocean warming) by helping to maintain reefs in a coral-dominated state via the removal of algae. However, as thermally sensitive ectotherms, rising thermal stress may also pose a serious threat to these fishes and the critical ecosystem functions they deliver. Here we evaluate the consequences of thermal stress on the capacity of a common herbivorous coral reef fish (Acanthurus triostegus) to control finely filamentous matrices of Caulerpa sertularioides and C. verticillata algae in Hawai'i, by characterizing in-vivo changes in metabolic demands, diurnal foraging rates, activity patterns and individual condition in a laboratory setting during winter (24.0±0.1°C), summer (27.5±0.1°C), and at the peak of a representative marine heatwave, (31.0±0.1°C). Rising temperatures caused significant increases in standard metabolic rate (from ~135 O2 kg-1 h-1 in winter to 224 O2 kg-1 h-1 at the peak of a marine heatwave), but not in the proportion of time spent active (~83-96%) or foraging (~2.4 bites min-1). Consequently, A. triostegus gained body mass during summer and winter, but lost ~0.8% body mass per day during the marine heatwave. Given marine heatwaves can last for weeks to months, these results indicate that while herbivorous coral reef fishes may continue to remove algae during periods of thermal stress, their ability to control many macroalga may be limited due to precipitous reductions in individual performance. Therefore, in addition to algal types, the thermal sensitivity in herbivorous reef fishes will need to be considered for the successful implementation of coral-algal management strategies in a warmer world.